(untitled) (Bangladesh Medical Journal, 2019)
Lymphoma can present with different type of serous effusion like pleural, pericardial and ascites and it signifies poor outcome .Pleural effusions are the most common type among these. Ascites and pericardial effusion are rare. Effusion can be can be caused by direct infiltration and impairment of the lymphatic drainage .Several investigations are available like study of the fluid for cytological, biochemical, immunohistochemistry and cytogenetics study to assess the qualities of effusion and make a quick diagnosis. This present case report will describe a case of 40 year old female patient with non-Hodgkin’s lymphoma (NHL) presented with generalized lymphadenopathy and chylous ascites and pleural effusion. Bangladesh Med J. 2018 May; 47 (2): 38-40